Sensitivity of gypsy moth Lymantria dispar (L., 1758) larvae from geographically removed populations to nucleopolyhedrovirus (Lepidoptera: Erebidae, Lymantriinae) - A. Ilyinykh (SHILAP Revista de lepidopterología, 2013)
Sensitivity of the gypsy moth (Lymantria dispar) larvae from geographical populations located in Khabarovsk and Novosibirsk, Russia, approximately 3800 kms apart, to its nucleopolyhedrovirus (LdNPV), was explored. Two isolates of LdNPV were used: “Altaiskiy” and “Novosibirskiy”. The larvae were reared on natural diets from egg- masses that were collected during outbreaks in the above mentioned regions. Part of the gypsy moth eggs, from which the larvae were grown, was used for diagnostics of occult LdNPV by PCR method. It was shown that 48 ± 5% and 91 ± 7% of the embryos from Novosibirsk and Khabarovsk populations, respectively, were virus-positive. The LC50 value in II-instar larvae from Khabarovsk, infected with both isolates of LdNPV, was approximately 8 times lower than in the larvae population from Novosibirsk. High sensitivity to LdNPV may be connected to the high level of occult virus detected in insects from the Khabarovsk population.